2019
DOI: 10.26444/aaem/92208
|View full text |Cite
|
Sign up to set email alerts
|

Domestic violence against seniors in rural areas of West Pomerania, Poland

Abstract: Introduction and objective. The study on domestic violence in rural areas of Western Pomerania (Poland), carried out in October 2017, aimed at determining the scale of domestic violence against the elderly, taking into account its 5 forms: psychological, physical, economic and sexual violence, as well as negligence. Materials and method. The research concept was implemented with the use of a representative sampling method by means of a questionnaire-based audit interview, and using research tools to measure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 1 publication
0
17
0
4
Order By: Relevance
“…Twelve studies reported on community- dwelling older adults [37, 39-41, 43-50], one on older adults living in nursing homes [38] and one study comprised a mixed sample [42]. Moreover, nine studies were based on random samples [37, 39-41, 44, 47-50], five were convenience samples [38, 42, 43, 45, 46]. Five of the random samples were nationally-representative [37, 40, 41, 44, 48].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twelve studies reported on community- dwelling older adults [37, 39-41, 43-50], one on older adults living in nursing homes [38] and one study comprised a mixed sample [42]. Moreover, nine studies were based on random samples [37, 39-41, 44, 47-50], five were convenience samples [38, 42, 43, 45, 46]. Five of the random samples were nationally-representative [37, 40, 41, 44, 48].…”
Section: Resultsmentioning
confidence: 99%
“…Five studies used the age of 60 as cut-off age for inclusion of older adults [42, 44, 46, 49, 50], five studies used 65 [37, 40, 41, 45, 47], one study 66 and one study used 70 [39]. Two studies did not report a cut-off age [38, 43]. Two studies only included older women [38, 50], one study included a majority of males [47], eight studies included a majority of female participants [37, 39-42, 44, 45, 49].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations